DC Current Harmonics Reduction in Multi-Inverter Topology - Reyes Moraga, Eduardo Felipe; Sarasiri, Nuapett; Pena, Ruben; Riedemann, Javier; Andrade Aguero, Ivan Eric; Blasco-Gimenez, Ramon; Jara, Werner (My University, 2022)
This letter presents a Space Vector Pulse Width Modulation (SVPWM) strategy for reducing the DC-link current harmonics in a multi- Voltage Source Inverter (VSI) topology with common DC-link bus. The DC current harmonic reduction is achieved by phase-shifting the PWM pattern of individual VSIs, with the inverters sharing the system total power. Simulation and experimental results are shown to validate the proposal.
Keywords: inverters; harmonic analysis; switches; space vector pulse width modulation; fourier series; time-frequency analysis; topology; pulse width modulated inverters; space vector pulse width modulation; harmonic analysis